2009
DOI: 10.1080/09637480902956594
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant activity in wild plant (Adenophora triphylla) leaves and roots as a potential source of functional foods

Abstract: Adenophora triphylla is commonly used in food materials and oriental medicine as an analgesic, anti-inflammatory, and antitussive. In the present study, the leaves and roots of A. triphylla were extracted with water and ethanol, respectively, to examine the extracts' in vitro antioxidant activities and total phenolic contents, as well as A. triphylla's potential as a new functional food source and safe and inexpensive supply of antioxidants. Different antioxidant tests were employed and the results were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
0
24
2
Order By: Relevance
“…These results are consistent with previous report that ATREE had antioxidant effects in vitro and in vivo. 19,36) This study adds more evidence that ATREE can play a role as an antioxidant reducing oxidative stress in internal body organs.…”
Section: Discussionmentioning
confidence: 90%
“…These results are consistent with previous report that ATREE had antioxidant effects in vitro and in vivo. 19,36) This study adds more evidence that ATREE can play a role as an antioxidant reducing oxidative stress in internal body organs.…”
Section: Discussionmentioning
confidence: 90%
“…However, low night temperature in TC showed a negative impact when compared with TA, suggesting elevation in night temperature leads to an increase in phenol [39]. Previous research showed a highest content of phenol (2.34 mg·g −1 , extracted by water) in this species [2]. Choi et al [9] also reported that the highest total phenolic amounts in the butanol extract (9.97 ± 0.73 mg·mL −1 ).…”
Section: Total Phenol and Flavonoid Accumulation Under Various Tempermentioning
confidence: 85%
“…It is also known as "Sha-shen" in Chinese and "Jan-dae" in Korean. The Chinese crude drug "shajin", extracted from the roots of A. triphylla, is an effective expectorant for the treatment of whooping cough and chronic bronchitis, and its pharmaceutical name is Radix Adenophorae [1,2]. Historically, A. triphylla was used as food to prevent obesity in Korea [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was reported that Adenophorae Radix contains triterpenoids (Du et al ., ; Yao et al ., ), phenolic glycosides (Kuang et al ., ; Koike et al ., ), sterols, alkaloids (Asano et al ., ) and essential oils (Miyazawa et al ., ). Anti‐obesity (Choi et al ., ), anti‐oxidant (Kim et al ., ; Kim et al ., ), anti‐cancer (Lee et al ., ) and anti‐bacterial (Huang, ) activities have been reported for the extract of Adenophorae Radix. Adenophora triphylla var.…”
Section: Introductionmentioning
confidence: 99%